Correlation between Serum IL-6 Level and Th17/Treg Ratio with Systemic Lupus Erythematosus Disease Activity - Familia, Adidia Carina; Yuliasih, Yuliasih; Rahmawati, Lita Diah (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2019)
Introduction: SLE pathophysiology shifted to a new paradigm which emphasizing the imbalance between Th17 and Treg. IL-6 is the main cytokine believed as the regulator of the balance between Th17 and Treg which play a big part in SLE pathophysiology and disease activity. The aim of this study was to determining the correlation between serum IL-6 level and Th17/Treg ratio with SLE disease activity on SLE inpatients of RSUD Dr. Soetomo Surabaya.Methods: This cross sectional study included newly diagnosed SLE patients based on American College of Rheumatology (ACR) 1997 revised criteria and confirmed by rheumatologist. All subjects underwent the same examination and assessment such as SLE disease activity was scored according to SLAM score, serum IL-6 level measured using ELISA, and Th17/Treg ratio where the expression Th17-Treg detected by flowcytometry method.Results: Thirty female subjects with active SLE had mean age 31,3 ± 10,46 years. The most frequent clinical manifestations were hematologic disorders and arthritis. Serum IL-6 level was significantly elevated in SLE patients compare to healthy subjects (200,61 pg/ml versus 45,9 pg/ml, p =0,028). Th17/Treg ratio were also significantly higher in SLE patients compared to healthy subjects (2,49 versus 1,20, p = 0,31). Th17/Treg ratio significantly correlated with SLE disease activity (r = 0,988; p<0,05). There were no significant correlation between serum IL-6 level with Th17/Treg ratio (r = -0,095; p>0,05) or even SLE disease activity (r = 0,066 ; p>0,05). Conclusion: Serum IL-6 level had no significant correlation with Th17/Treg ratio or SLE disease activity. We found significant correlation between Th17/Treg ratio with SLE disease activity.